A Fast and Efficient Estimation of the Parameters of a Model of Accident Frequencies via an MM Algorithm - Issa Cherif Geraldo; Edoh Katchekpele; Tchilabalo Abozou Kpanzou (Journal of Applied Mathematics, 2023)
In this paper, we consider a multivariate statistical model of accident frequencies having a variable number of parameters and whose parameters are dependent and subject to box constraints and linear equality constraints. We design a minorization-maximization (MM) algorithm and an accelerated MM algorithm to compute the maximum likelihood estimates of the parameters. We illustrate, through simulations, the performance of our proposed MM algorithm and its accelerated version by comparing them to Newton-Raphson (NR) and quasi-Newton algorithms. The results suggest that the MM algorithm and its accelerated version are better in terms of convergence proportion and, as the number of parameters increases, they are also better in terms of computation time.